Post Stroke, Is Perimetry Necessary? A Case Report: Poster Presentation - Case Report - Resident - AULIA PURNAMA EFFENDI; Bobby Ramses Erguna Sitepu (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Stroke are generally associated with peripheral visual field loss. Three out of four stroke patients report some form of disability, one of which is visual impairment. Approximately 16% of these patients have a homonymous visual field defect poststroke. These vision problems can lead to difficulty carrying out a lot of daily tasks and activities, such as driving. This report tries to define the diagnostic flow to determine the exact type and lesion. Case Illustration : Male, 61 years old, came to Universitas Sumatera Utara Hospital with visual field loss in both eyes. Two months ago, he was diagnosed with ischemic stroke and treated with Aspirin 80 mg, with no limbs disability right now. He also had hypertension and treated with Amlodipine 10 mg. VOD: 6/60 with BCVA S-2.00 6/7,5, VOS: 6/60 with BCVA S-2.00 6/7.5. With confrontation test and perimetry, defect was found in medial visual field OD and lateral visual field OS. Hess screen and Amsler Grid was normal. Head CT-Scan was performed with multiple infarcts, mainly in right occipital lobe. The patient was diagnosed with Incomplete Hemianopia, Left Congruous Homonymous Hemianopia with Macular Sparing, and treated with Citicholine 1000 mg once daily. Discussion Conclusion : In stroke patients with homonymous visual field loss, visual field testing with detailed evaluation of visual field defect can determine the lesion location, and neuro-radiological imaging was necessary to assess visual pathway. It’s important for educate the patients, diagnostic and prevent the stroke recurrent.